ANALISIS PERBEDAAN KEPUASAN KONSUMEN ONLINE SHOP ANTARA TOKOPEDIA DAN SHOPEE PADA MASYARAKAT KOTA SANGATTA KABUPATEN KUTAI TIMUR: Meita Sondang Riski Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta Email : meitasondang@yahoo.com Kaharuddin Sekolah Tinggi Ilmu Manajemen Indonesia - Samarinda Jl. Dr. Muhammad Yamin no 78 RT VII Samarinda 75119 email : kahar_asa@yahoo.com - Riski, Meita Sondang (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2024)
The aim of the research is to analyze the differences in online shop consumer satisfaction between Tokopedia and Shopee in the people of Sangatta City, East Kutai Regency. This research is quantitative research and the calculations use the SPSS program application. Version 21. Hypothesis testing uses the Mann Whitney test, used with the aim of determining whether there is a difference in the averages of two unrelated samples. The test results above can be seen from the Asymp Sig (2 tailed) value, namely 0.001. Based on the Test Statistics output, it is known that the Asymp Sig (2tailed) value is 0.001 < 0.05, so it can be concluded that the hypothesis is accepted. Thus, it can be said that there is a difference in satisfaction between online shop consumers between Tokopedia and Shopee in the people of Sangatta City, East Kutai Regency.